(untitled) (Emancipação, 2024)
The present study aims to reflect on how games can enhance understanding of human and social rights while ethically impacting various areas. It employs an interdisciplinary qualitative analysis that combines theories from anthropology, sociology, and education sciences to explore games’ social and cultural functions, focusing on digital games under the lens of ludocapitalism. The study revealed that digital games, through mechanisms such as gamification, have the potential to enhance cognitive and social skills while simultaneously raising significant ethical concerns related to behavioral manipulation and the loss of player autonomy. It concludes that although digital games offer significant educational and social development opportunities, it is essential to implement ethical gaming practices to avoid risks of manipulation and reinforcement of social inequalities.